EFFECTIVENESS OF FISH LANDING BASE (PPI) BUNTOK SUPPLY CHAIN IN THE MARINE CAPTURE FISHERIES IN THE DISTRICT PUBLIC LANDS OF SOUTH BARITO, CENTRAL KALIMANTAN - Rismutia Hayu Deswati (Widyariset, 2015)
Barito River is one of the typology of inland waters that has the potential of abundant fish resources as much as 3-4 million tons of fish everyday. Fisheries marketing purposes in the District of South Barito are divided into two, they are inside and outside the district. This study aims to determine the supply chain system of the fish and examine measures to improve the effectiveness of PPIs in the distribution of fisheries in the South Barito regency. Data were collected through observation and interviews with key informants. The method of analysis used in this study with supply chain analysis and gap analysis described descriptively. From the research, it can be concluded that it is still not optimal in the presence of PPI Buntok distribution fisheries in the South Barito regency which recorded only 15% of fish catches are marketed in PPI Buntok while 85% is marketed outside the district. It istherefore necessary building repairs PPI adequate physical and managerial improvement in the management of the PPI